Оптимізація вибору методу гормональної контрацепції у жінок з надлишковою масою тіла - Грідіна, Ірина Борисівна; Gridina, I. B. (Запорізький державний медичний університет, 2018)
Розробка та впровадження методів збереження репродуктивного здоров’я жінки, зокрема методів контрацепції, визнані пріоритетним напрямом сучасної медицини, який постійно розвивається в усьому світі. Особливий інтерес привертає стан надлишкової ваги в жінок, оскільки він є пограничним, і чіткі показання та протипоказання до використання в них гормональної контрацепції досі відсутні. Саме тому метою дослідження стало зменшення негативних наслідків використання гормональної контрацепції в жінок з надлишковою масою тіла та покращення якості їх життя шляхом удосконалення алгоритму підбору методу гормональної контрацепції на підставі визначення їх негативних проявів і лікувальних неконтрацептивних ефектів. The growing epidemic of obesity attracts attention of accoucheurs and gynaecologists for a long time. There exists many research papers concerning this problem. However, the questions of the efficacy of hormonal contraception are far from being solved. The majority of gynaecologists and family doctors in particular suppose overweight and obesity as contra-indications for prescribing hormonal conraceptives that leads to the increase of level of unintended pregnancies and abortions. Hormonal contraception is a specific gynaecological question. As a rule it is applied on the background of some somatopathies. It must be examined within the framework of comorbidity. Therefore the executed research undoubtedly attracts attention as from the scientific so as from the practical point of view. All the above mentioned is the evidence of the medical and social meaningfulness of the problem, viability of the study. It stipulates research actuality and states the thesis as actual and modern.
Optimization of choice of hormonal contraception method for overweight women-qualifying scientific study
Keywords: надлишкова вага; контрацепція; якість життя; інтравагінальне гормональне кільце, інсулінорезістентність; інсулінорезістентність; overweight; contraception; quality of life; intravaginal hormonal ring; insulin resistance